Implementation of project-based learning theme blue my sky is healthy my earth to increase environmental literacy - Wicaksono, Tegar Sindu; Ismawati, Riva; Muhlisin, Ahmad (Edu Sains: Jurnal Pendidikan Sains & Matematika, 2024)
This research aims to analyze the effect of the Project-Based Learning theme Blue My Sky is Healthy My Earth to increase environmental literacy. The research carried out was quasi-experimental quantitative research using statistical tests on numerical data. The overall N-gain value of environmental literacy in the experimental class that uses the Project-Based Learning model is 0.76. From the research results, it can be concluded that the hypothesis test value from the data results is fulfilled, namely, tcount 5.657 > ttable 2.012 so there is a difference in increasing environmental literacy between students who receive the Project-Based Learning model and the conventional learning model. The category of increasing environmental literacy is high. The value of each environmental literacy indicator is 0.73 for the ecological knowledge indicator in the high category, 0.81 for the environmental skills indicator in the high category, and 0.75 for the attitude towards the environment indicator in the high category.